A re-examination of process–outcome relations in cognitive therapy for depression: Disaggregating within-patient and between-patient effects. (3rd July 2016) - Sasso, Katherine E.; Strunk, Daniel R.; Braun, Justin D.; DeRubeis, Robert J.; Brotman, Melissa A.
Abstract: Objective: We previously examined alliance and therapist adherence as predictors of symptom change. Applying a new analytic strategy, we can ensure that any relations identified were not attributable to stable patient characteristics.Method: Participants were 57 depressed cognitive therapy patients. We disaggregated within- and between-patient variation in process measures.Results: Between-patients, variability in adherence to Cognitive Methods and Negotiating/Structuring predicted patients' symptom change. Within-patients, only variability in ratings of adherence to Cognitive Methods predicted next-session symptom change.Conclusions: Relations involving between-patient process variables are potentially attributable to stable patient characteristics. However, the relation of within-patient Cognitive Methods and session-to-session symptom change cannot be attributed to stable characteristics and is consistent with a causal relationship.